Transcriptomic Analysis of circRNAs in the Peripheral Blood of Nonarteritic Anterior Ischemic Optic Neuropathy - Han, Xiao; Wang, Xinling; Han, XIao; Zhang, Jiaming; Hou, Naifang; Xu, Haoyan; Xu, Xinling; Suo, Jinshan; Zheng, Yanwen (BioMed research international, 2020)
The aim of the study is to explore the expression profile variation of circular RNAs (circRNAs) in the peripheral blood of subjects with nonarteritic anterior ischemic optic neuropathy (NAION) and without NAION, to analyze the differential expression results, and to predict the role of circRNAs in disease development, providing novel ideas and methods for treatment and diagnosis. High-throughput sequencing to explore the expression profiles of RNAs in the peripheral blood of 6 NAION patients and 5 healthy controls was applied. Quality control obtained the advanced data from the original data by ticking out the unqualified data. Then, cluster analysis, volcano plot, coexpression network, and protein-protein interaction network (PPI) were performed. Gene ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway were used to analyze the whole expressed genes. Lastly, the quantitative real-time Polymerase Chain Reaction (qRT-PCR) was used to verify those significantly differentially expressed circRNAs and do some bioinformatics analysis and prediction in 12 NAION patients and 12 controls. There were significant differences in the expression of 49 circRNAs in the peripheral blood of NAION patients, in which there were 24 upregulations and 25 downregulations (variation folds>2 and P<0.05), and it was confirmed that hsa_circ_0005583, hsa_circ_0003922, hsa_circ_0002021, and hsa_circ_0000462 were significantly downregulated (variation folds>2 and P<0.05), especially hsa_circ_0005583 which was the most significantly changed one (P<0.001), and are related to processes such as neurodegeneration, oxidative stress, immunity, and metabolism. The expression profile of circRNAs in the peripheral blood of NAION patients is significantly changed, enriching our understanding of the disease.